The integrated analysis of SIRT family expression, prognostic value, and potential implications in childhood acute lymphoblastic leukemia - Xu, Xusan; Wang, Zhendong; Wang, Xiaoxia; Zhang, Wensen; Luo, Zhengqiang; Zheng, Xiaomei; Pan, Ronghua; Fu, Ying; Wang, Yajun; Huang, Guochun; Chen, Riling; Ma, Guoda (Frontiers in Oncology, 2025)
BackgroundAcute lymphoblastic leukemia (ALL) is a rapidly progressive hematological malignancy caused by the dysregulated proliferation and abnormal differentiation or differentiation block of lymphoid precursors. The sirtuin family, as a highly conserved class of protein deacetylases dependent on NAD+, has been widely reported in leukemia. However, there has been no research on the prognostic value and molecular functions of the sirtuin protein family in pediatric ALL.MethodsIn this study, we employed the Therapeutically Applicable Research to Generate Effective Treatments (TARGET), Genotype-Tissue Expression (GTEx), Encyclopedia of RNA Interactomes (ENCORI), Cancer Therapeutics Response Portal (CTRP), and STRING databases as well as R language to explore and visualize the role of the sirtuin family in childhood ALL. The receiver operating characteristic (ROC) curve was performed to investigate their diagnostic value, while the Kaplan–Meier survival curve and Cox regression analysis were utilized to test their prognostic value. Additionally, we conducted Pearson correlation analysis to explore the association between sirtuin family mRNA expression and DNA methylation.ResultsOur results indicate that sirtuin family mRNA expression is dysregulated in pediatric ALL. The ROC curve revealed that SIRT1 and SIRT4 expression is highly sensitive and specific in diagnosing childhood ALL (AUC > 85.0%, p < 0.001). While higher SIRT1, SIRT4, SIRT5, and SIRT7 expression was related to higher event-free survival rate and overall survival (OS) rate, higher SIRT2 expression was associated with lower event-free survival rate and rate in childhood ALL (p < 0.05). Moreover, Cox regression and nomogram analyses suggested that SIRT1 mRNA expression is an independent factor for pediatric ALL. Subtype analysis revealed that SIRT1 primarily functions in B-cell precursor ALL (B-ALL). Furthermore, SIRT1 is involved in various RNA splicing and acetyltransferase complex in B-ALL. The data from the CTRP database and the Cell Counting Kit-8 (CCK-8) experiment suggested that SIRT1 increased the sensitivity of B-ALL cell lines to vincristine. In vitro experiments demonstrated that SIRT1 inhibits invasion activity in B-ALL cell lines (NALM6 and REH).ConclusionsSIRT1 represents a potential prognostic biomarker and therapeutic target in childhood B-ALL.